2024
DOI: 10.2147/ccid.s329442
|View full text |Cite
|
Sign up to set email alerts
|

Practical Use of Upadacitinib in Patients with Severe Atopic Dermatitis in a Real-World Setting: A Systematic Review

Luciano Ibba,
Luigi Gargiulo,
Carlo Vignoli
et al.

Abstract: Upadacitinib is a selective Janus kinase inhibitor approved for the treatment of severe atopic dermatitis (AD). This systematic review aims to summarize the most recent data in terms of effectiveness and safety of upadacitinib in the treatment of severe AD in a real-world setting. The review included a comprehensive search of databases, including PubMed, Google Scholar and Web of Science, according to Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. The literature search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The effectiveness of upadacitinib was robust, regardless of previous dupilumab exposure, and the study reported no serious AEs. Ibba L et al's systematic review further confirms the long-term effectiveness and safety of upadacitinib for severe AD in real-world studies [17]. Through these comparative analyses, the vital role of upadacitinib in the AD treatment landscape is reinforced, endorsing its application as a primary treatment option for achieving long-term disease control.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The effectiveness of upadacitinib was robust, regardless of previous dupilumab exposure, and the study reported no serious AEs. Ibba L et al's systematic review further confirms the long-term effectiveness and safety of upadacitinib for severe AD in real-world studies [17]. Through these comparative analyses, the vital role of upadacitinib in the AD treatment landscape is reinforced, endorsing its application as a primary treatment option for achieving long-term disease control.…”
Section: Discussionmentioning
confidence: 84%
“…Reports on the long-term effectiveness and safety of upadacitinib in managing AD in real-world clinical studies are increasing, illustrating the sustained therapeutic potential of the drug. This is highlighted in studies from Italy, such as those by Chiricozzi A et al 2023 andGargiulo et al 2023, as well as the systematic review by Ibba L et al [17] and others [8,10,[18][19][20]. Chiricozzi A et al detailed the outcomes for 146 patients with moderateto-severe AD, most of whom (87.0%) received upadacitinib as monotherapy [8].…”
Section: Discussionmentioning
confidence: 99%